Implementasi Vigenere Cipher dalam Keamanan Email Untuk Keamanan pada Pesan Teks - Fuadi, Nafal Mumtaz; Gibran, Daffa; Firhansyah, Wahyu; Muhana, Hamim (Prosiding Sains dan Teknologi, 2024)
In the current digital era, information security is becoming increasingly crucial. Email, as one of the most commonly used forms of digital communication, often contains confidential or sensitive information. Therefore, email security is of utmost importance to safeguard the confidentiality of text messages. One technique that can be employed to enhance email security is the Vigenère Cipher, a classical encryption method that has been utilized for centuries. This research discusses the implementation of the Vigenère Cipher in the context of email security with the goal of protecting text messages. In the current digital era where sensitive information is frequently transmitted via email, email security is becoming more critical. The Vigenère Cipher, as a classical encryption method, is utilized in this study to enhance email security by encrypting text before it is sent via email. The study also explores the challenges and benefits of using the Vigenère Cipher in the realm of email security. By applying the Vigenère Cipher in email security, this research aims to contribute to a practical understanding of the implementation of classical encryption techniques in the modern digital communication environment.